ANALYSIS OF THE IMPACT OF CHATGPT ON LEARNING PRODUCTIVITY OF ISLAMIC EDUCATION STUDENTS - Ahmad Baiquni; Tri Indah Rusli; Juhardin Juhardin; Lely Kholida; Arsam Arsam (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2025)
This study aimed to investigate the impact of ChatGPT use on students’ learning productivity and provide recommendations for its effective utilization. Employing a descriptive qualitative approach, data were collected through observation, documentation, and semi-structured interviews with 12 purposively selected active users. The data analysis employed the Miles and Huberman interactive model, emphasizing data reduction, data display, and conclusion drawing. The findings revealed that ChatGPT contributed significantly to enhancing efficiency in learning processes, improving conceptual understanding, and stimulating creativity among students. However, the study also uncovered several drawbacks, such as a decline in critical thinking skills, reduced motivation for independent literacy practices, and an increased tendency toward technological dependence. Within the specific context of Islamic Religious Education, the research further identified that some ChatGPT-generated responses were less accurate or misaligned with authoritative references, necessitating additional validation by educators and learners. The implications of this research highlight that ChatGPT can serve as a valuable supportive learning tool if applied proportionally. To achieve holistic and high-quality learning, students and teachers are advised to use ChatGPT with careful attention to information validation, cultivation of critical thinking, and strategies that minimize overreliance on technological assistance.